ANTARA KECERDASAN ARTIFISIAL DAN KEBUTUHAN PENALARAN HUKUM DALAM PENYUSUNAN JOINT VENTURE AGREEMENT - Gisca Nurannisa (Veritas et Justitia, 2025)
The development of Artificial Intelligence (AI) technology has made a significant contribution to the legal field, particularly in the drafting of business contracts such as Joint Venture Agreements (JVAs). AI assists in researching necessary data and drafting contractual clauses in JVAs. Although AI greatly facilitates contract drafting, it has inherent limitations because it cannot fully accommodate the legal context, or the specific needs of the parties involved in a transaction. This article examines the use of AI in contract drafting through the lens of Roscoe Pound’s theory of Mechanical Jurisprudence. Pound criticized the rigid application of law by judges, which this study analogizes to AI-generated contract clauses that are standardized and insufficiently responsive to the parties’ particular interests. The research is conducted through a literature review using a normative and prescriptive legal approach. The study concludes that AI should be used only as an auxiliary tool rather than as a primary reference in contract drafting, especially for complex business contracts such as JVAs. This is because AI-generated outputs are not the product of human legal reasoning capable of incorporating legal context, social norms, party interests, and considerations of justice. Consequently, such outputs remain rigid and require careful analysis and review by human contract drafters.